2022
DOI: 10.1111/imr.13157
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role for metabolism in fueling neutrophilic inflammation

Abstract: Neutrophils are a critical element of host defense and are rapidly recruited to inflammatory sites. Such sites are frequently limited in oxygen and/or nutrient availability, presenting a metabolic challenge for infiltrating cells. Long believed to be uniquely dependent on glycolysis, it is now clear that neutrophils possess far greater metabolic plasticity than previously thought, with the capacity to generate energy stores and utilize extracellular proteins to fuel central carbon metabolism and biosynthetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 142 publications
(304 reference statements)
1
12
0
Order By: Relevance
“…Despite the low frequency of infection, RSV induced a similar inflammatory response as seen with other respiratory viruses, such as SARS-CoV-2 and IAV, with clear evidence of leukocyte recruitment and monocyte and T cell driven vasculitis and perivascular/peribronchial infiltration 84 . Daprodustat treatment dampened these inflammatory responses, although the recruitment of neutrophils was maintained, in line with earlier reports on hypoxia driving neutrophilic inflammation 85 . Preliminary experiments in mice infected with the genetically related pneumovirus of mice (PVM), a natural pathogen of rodents, support our findings with hRSV and showed a reduced frequency of infected cells and a less intense inflammatory response following Daprodustat treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the low frequency of infection, RSV induced a similar inflammatory response as seen with other respiratory viruses, such as SARS-CoV-2 and IAV, with clear evidence of leukocyte recruitment and monocyte and T cell driven vasculitis and perivascular/peribronchial infiltration 84 . Daprodustat treatment dampened these inflammatory responses, although the recruitment of neutrophils was maintained, in line with earlier reports on hypoxia driving neutrophilic inflammation 85 . Preliminary experiments in mice infected with the genetically related pneumovirus of mice (PVM), a natural pathogen of rodents, support our findings with hRSV and showed a reduced frequency of infected cells and a less intense inflammatory response following Daprodustat treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Despite recent advances in the field of immunometabolism, our understanding of neutrophil metabolism remains incomplete. Previous studies have indicated that neutrophils primarily rely on glucose as their primary carbon source for metabolic processes [40]. However, emerging evidence suggests that neutrophils also utilize a variety of other nutrients, including amino acids, carbohydrates, proteins, and lipids, to generate energy [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect has already been described for activated macrophages [81], in trained monocytes [82], in monocyte-derived dendritic cells [83], in neutrophilic inflammation [84], and activated lymphocytes [85]. The main regulating factors driving this metabolic reprogramming from oxidative phosphorylation to fermentative glycolysis are hypoxia inducible factor (HIF)-1α and lactate.…”
Section: Introductionmentioning
confidence: 95%